A cell-intrinsic role for CaMKK2 in granulocyte lineage commitment and differentiation - Teng, Ellen C. (Society for Leukocyte Biology, 2011)
Granulocytes serve a critical function in host organisms by recognizing and destroying invading microbes, as well as propagating and maintaining inflammation at sites of infection. However, the molecular pathways underpinning the development of granulocytes are poorly understood. Here, we identify a role for CaMKK2 in the restriction of granulocytic fate commitment and differentiation of myeloid progenitor cells. Following BMT, engraftment by Camkk2(−/−) donor cells resulted in the increased production of mature granulocytes in the BM and peripheral blood. Similarly, Camkk2(−/−) mice possessed elevated numbers of CMP cells and exhibited an accelerated granulopoietic phenotype in the BM. Camkk2(−/−) myeloid progenitors expressed increased levels of C/EBPα and PU.1 and preferentially differentiated into Gr1(+)Mac1(+) granulocytes and CFU-G in vitro. During normal granulopoiesis in vivo or G-CSF-induced differentiation of 32D myeloblast cells in vitro, CaMKK2 mRNA and protein were decreased as a function of time and were undetectable in mature granulocytes. Expression of ectopic CaMKK2 in Camkk2(−/−) CMPs was sufficient to rescue aberrant granulocyte differentiation and when overexpressed in 32D cells, was also sufficient to impede granulocyte differentiation in a kinase activity-dependent manner. Collectively, our results reveal a novel role for CaMKK2 as an inhibitor of granulocytic fate commitment and differentiation in early myeloid progenitors.